Adherence to Antihypertensive Medication in Patients with Hypertension in Indonesia - Tania Tania; Vycke Yunivita; Afiatin Afiatin (International Journal of Integrated Health Sciences, 2019)
Objective: Adherence to medication is crucial for hypertension patients in order to control and prevent complications. This study aimed to describe the adherence to antihypertensive drugs among patients with hypertension in Bandung District, West Java, Indonesia.Methods: This was a cross-sectional observational study on patients with hypertension in the work area of Cileunyi Public Health Center (PHC), Bandung District, West Java, Indonesia. The inclusion criteria used were patients with hypertension who were prescribed an antihypertensive drug by a physician, above 18 years old, and had been using an antihypertensive medication for at least two months before the study. Data were obtained through interviews during the month of July to August 2018 using a modified MMAS-8 questionnaire of the Morisky Medication Adherence Scale (MMAS-8), which includes Likert-type scale questions. Data collected were then analyzed using the Rasch Model, and the mean logit person was used as a cut off between adherence and non-adherence categories.Results: A total of 75 patients with hypertension were recruited. The prevalence of adherence to medication was 59%. Most patients who adhered to the medication were > 55 years old (31%),  female (59%), had been diagnosed with hypertension for < 5 years (31%), and received support from family/social environment (40%).Conclusion: Many factors support the adherence to antihypertensive medication, including age, gender, time of hypertension diagnosis, and support from family or social environment. The adherence to antihypertensive medication among patients with hypertension visited Cileunyi Primary Health Care, Bandung District, West Java, Indonesia is good.